2001
DOI: 10.1002/jpp.311
|View full text |Cite
|
Sign up to set email alerts
|

Excited states of four hemes in a c-type cytochrome subunit of the photosynthetic reaction center ofRhodopseudomonas viridis: SAC-CI calculations

Abstract: The excited states of four hemes, c‐552, c‐554, c‐556, and c‐559, in a c‐type cytochrome subunit of the photosynthetic reaction center (PSRC) of Rhodopseudomonas (Rps.) viridis were studied using the symmetry‐adapted cluster (SAC)‐configuration interaction (CI) method. c‐552 has two imidazole ligands, while the other three hemes have imidazole and methionine ligands. The electronic states of these four hemes are affected significantly by both the ligands and protein and water environments. The ligand effect cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…We remind the reader that numerous theoretical studies of different porphyrins have been carried out. In recent years the emphasis has shifted from semiempirical calculations 19,20 to more sophisticated ab initio wave function and, in particular, density functional theory (DFT) approaches. Nakatsuji et al applied symmetry-adapted-cluster (SAC) and SAC−CI (configuration interaction) methods to free-base porphyrins (FBP) 21 and to a number of porphyrin-type molecules , in order to interpret the singlet−singlet absorption spectrum. Rubio and Serrano-Andrés , have calculated the singlet−singlet absorption spectra of those compounds making use of the CASPT2.…”
Section: Resultsmentioning
confidence: 99%
“…We remind the reader that numerous theoretical studies of different porphyrins have been carried out. In recent years the emphasis has shifted from semiempirical calculations 19,20 to more sophisticated ab initio wave function and, in particular, density functional theory (DFT) approaches. Nakatsuji et al applied symmetry-adapted-cluster (SAC) and SAC−CI (configuration interaction) methods to free-base porphyrins (FBP) 21 and to a number of porphyrin-type molecules , in order to interpret the singlet−singlet absorption spectrum. Rubio and Serrano-Andrés , have calculated the singlet−singlet absorption spectra of those compounds making use of the CASPT2.…”
Section: Resultsmentioning
confidence: 99%
“…We have been studying electron transfer in the photosynthetic reaction center in Rhodopseudomonas viridis . In a series of studies on the absorption spectrum, SAC−CI calculations gave an ab initio assignment for the reaction center. ,, An SAC−CI study revealed that the L-branch preference of the electron transfer is mostly due to electronic factors. , A perturbation-theoretical method was applied to the electronic factor for electron transfer from H to UQ along both the L and M chains 39 and for electron transfer from the cytochrome c unit to the oxidized special pair P + …”
Section: Introductionmentioning
confidence: 99%